PENGARUH LEVERAGE, RISIKO SISTEMATIK, FIRM GROWTH DAN KUALITAS AUDIT TERHADAP EARNINGS RESPONSE COEFFICIENT (ERC) (Studi Pada Perusahaan Sektor Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia Pada Tahun 2013-2015) - Ria Nelly Sari; Pipin Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research aims to examine the effect of leverage, systematic risk, firm growth and audit quality on Earnings Response Coefficient (ERC). The population is all property and real estate companies that listed on the Indonesia Stock Exchange periode 2013 to 2015. The number of samples is 47 companies that are determined by purposive sampling method. This research uses panel data regression analysis using Eviews 10 software and Microsoft Excel 2016. The result of this research show leverage that is proxied by DER and firm growth that is proxied by PBV effect on ERC, while systematic risk that is proxied by beta and audit quality that is proxied by size of KAP does not effect on ERC. Based on the calculation of coefficient determination (R2 ) was 0.1919. Leverage, systematic risk, firm growth and audit quality on ERC simultaneously giving effect was 19,2%. While the remaining 80,8% is influenced by other independent variabel that are not observed in this research.Keywords : Leverage, Systematic Risk, Firm Growth, Audit Quality, and Earnings Response Coefficient (ERC). PENDAHULUAN Laporan keuangan adalah suatu penyajian terstruktur dari posisi keuangan dan kinerja keuangan suatu entitas. Laporan keuangan bertujuan untuk menyediakan informasi yang menyangkut posisi keuangan, kinerja, serta perubahan posisi keuangan yang bermanfaat bagi sebagian besar pemakai